Comparative influence of immobilization medium and mutation on EPS - production by L. Plantarum MK 02 isolated from fermented milk - B. Adebayo-Tayo; O. Agidigbi; S. Alao (Trakia Journal of Sciences)
PURPOSE: Comparative effect of mutation and immobilization on EPS-production L. plantarum MKO2 was investigated. METHODS: L. plantarum strain and EPS produced by wild, mutants, immobilized and unimmobilized strains was characterized. RESULTS: The EPS production by the Wild type L. plantarum MK O2 and the Mutant L. plantarum Muv 11 and Muv 12 ranged from 209.89 – 268.19 mg/l in which the highest value was produced by Mutant L. plantarum Muv 12. EPS production on immobilization in sodium alginate ranged from 225.00 – 263.44mg/l. Mutant L. plantarum Muv 12 had the highest while Wild type L. plantarum MK O2 had the least. EPS – production by un –immobilized Wild type L. plantarum MK O2 and Mutant L. plantarum Muv 11 and Muv 12 ranged from 215.00 – 255.00 mg/l. Immobilization in sodium alginate favoured EPS-production by wild type L. plantarum MK O2 (225.00 mg/l) and Mutant L. plantarum Muv 12 (272.00 mg/l) while immobilization in agar matrix favoured EPS –production by Mutant L. plantarum Muv 11 (265.67 mg/l). FT-IR spectroscopy of the EPS showed the presence of the varying degrees of functional groups which are usually associated with polysaccharides, thus confirming the EPS. CONCLUSION: Mutation and immobilization increased EPS production by the L. plantarum strains.